The Comparison of Analgesics and Kinesiological Taping in Rib Fractures - Cakmak, Muharrem; Aydin, Siyami; Balci, Akin Eraslan (Springer India, 2021)
Pain is the most common symptom of rib fractures. In pain control, narcotic and non-narcotic agents, intercostal blockage, epidural catheter, and even rarely surgical intervention and reduction can be applied. The kinesiology taping method has an analgesic effect by reducing edema and inflammation, activating sensory stimuli, descending inhibitory mechanisms, and regulating superficial and deep fascia functions. It has a wide range of indications in pain control including musculoskeletal system mostly. However, no studies have been reported on the application of kinesiology tape in rib fractures. In our study, we aimed to share the results of cases who received oral/parenteral analgesic treatment and those who underwent kinesiology taping. A series of 46 cases with rib fractures due to thoracic trauma were analyzed. The verbal pain scores of group 1 (G1) who had a single rib fracture and to whom kinesiology taping was performed and group 2 (G2) who received analgesic treatment were evaluated. The pain scores of the cases in both groups at the 30th minute; 1st, 3rd, 6th, 12th, and 24th hours; and 3rd day were analyzed. Results were evaluated by Mann-Whitney U tests. p<0.05 was considered significant. There were a total of 23 cases in each group. The mean age of G1 was 53.26 SD17.55 years. The mean age of G2 was 55.86 SD16.37. The mean pain score in G1 after the tape application was 4.78 SD0.79 at the 30th minute, 4.43 SD0.58 at the first hour, 4.08 SD0.59 at the 3rd hour, 3.91 SD0.66 at the 6th hour, 3.86 SD0.75 at the 12th hour, 3.69 SD0.82 at the 24th hour, and 3.82 SD0.57 on day 3. After analgesic treatment, the mean pain score of G2 was found as 7.47 SD0.51 at the 30th minute, 6.86 SD0.34 at the first hour, 6.56 SD0.72 at the 3rd hour, 6.52 SD0.51 at the 6th hour, 5.95 SD0.36 at the 12th hour, 6 at the 24th hour, and 5.21 SD0.51 on day 3. When the pain scores of G1 and G2 were compared, it was found that kinesiology tape was significantly significant (p<0.00001, p<0.05). In conclusion, in reducing pain complaints affecting the quality of life in cases with rib fractures due to thoracic trauma, the application of kinesiology tape significantly reduced the need for analgesics and even eliminated the need in the long term. Following this study, we think that in patients with more fractures or bilateral rib fractures, larger randomized studies should be performed and routine treatment should be included.
Keywords: Analgesic; Fracture; Rib; Kinesiology taping